SOCIAL CARE CHARACTER BUILDING IN EARLY CHILDHOOD IN CIREBON CITY - Meliani, Fitri; Widadiyah, Qorina; Marliani, Lina; Gita, Meylina (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This article aims to examine how schools build social care characters in early childhood through storytelling and market day. This is a preventive effort against the decline in social skills and empathy in early childhood, along with the challenges of technological development. This research uses a descriptive qualitative approach with the type of field research (field research) in the context of a case study. The subjects of this study were teachers of classes A and B. The methods used were observation, interviews (to principals and teachers) and documentation at Taud Saqu Al Binaa Kota Cirebon. The results showed that Taud Saqu Al Binaa conducted social care character education at early childhood by compiling programs in the form of storytelling of the Palestinian people's conflict and market day in the context of fundraising (philanthropy) to help Palestinians who are experiencing conflict with Israel. One of the attempts to build social care to children is by integrating this kind of behavior in their daily lives so as to make them get accustomed to the attitudes and actions. The process of inculcating social care characters in students, there are two stages: first is the example of the teacher; second is habituation that must be done continuously. Meanwhile, in strengthening the two stages, several programs, namely: philanthropy, takjil on the road, donations for victims of natural disasters, social services, distribution of qurban meat and qurban food security